Dual inhibition of VEGFR and EGFR signaling reduces the incidence and size of intestinal adenomas in Apc(Min/+) mice. - Alferez, D; Wilkinson, R; Watkins, J; Poulsom, R; Mandir, N; Wedge, SR; Pyrah, I; Smith, N; Jackson, L; Ryan, A; Goodlad, R (2008)
Both the epidermal growth factor (EGF) and the vascular endothelial growth factor (VEGF) pathways are associated with intestinal cancer, and therapeutic approaches targeting either EGF receptor (EGFR) or VEGF receptor (VEGFR) signaling have recently been approved for patients with advanced colorectal cancer. The Apc(Min/+) mouse is a well-characterized in vivo model of intestinal tumorigenesis, and animals with this genetic mutation develop macroscopically detectable adenomas from approximately 6 weeks of age. Previous work in the Apc(Min/+) mouse has shown that therapeutic approaches targeting either VEGFR or EGFR signaling affect predominantly the size or number of adenomas, respectively. In this study, we have assessed the effect of inhibiting both these key pathways simultaneously using ZD6474 (Vandetanib, ZACTIMA), a selective inhibitor of VEGFR and EGFR tyrosine kinases. To assess the effects of ZD6474 on early- and later-stage disease, treatment was initiated in 6- and 10-week-old Apc(Min/+) mice for 28 days. ZD6474 markedly reduced both the number and the size of polyps when administered at either an early or a later stage of polyp development. This reduction in both adenoma number and size resulted in a total reduction in tumor burden in the small intestine of nearly 75% in both studies (P < 0.01). The current data build on the concept that EGFR-dependent tumor cell proliferation and VEGF/VEGFR2-dependent angiogenesis and survival are distinct key mechanisms in polyp development. Pharmacologic inhibition of both signaling pathways has significant antitumor effects at both early and late stages of polyp development. Therefore, targeting both VEGFR- and EGFR-dependent signaling may be a beneficial strategy in early intestinal cancer.